«Scegli dunque la vita» (Dt 30,19): legge, fede e libertà nella rilettura di Rm 10,4-6 - Puca, Bartolomeo (Rassegna di teologia, 2021)
In the following article, daring to dialogue between the texts, we are led into a lively exegetical and theological debate about the interpretation of Rm 10,4-6 in its argumentative context (Rm 9,30-10,21), wondering if the invitation to "choose life" (cf Dt 30:19) does resonate, in this passage from the Epistle to the Romans, in terms of inviting everyone, Jews and pagans, to choose Christ in the faith. The apostle Paul interprets the texts founded on the covenant of God with his people to show how the law finds its end in Christ, as accomplished by him. In this sense, Christ becomes the necessary choice in order to reach the life promised by God. (English)